Scutellaria barbata D.Don and Hedyotis diffusa Willd herb pair combined with cisplatin synergistically inhibits ovarian cancer progression through modulating oxidative stress via NRF2-FTH1 autophagic degradation pathway - Xue Sui; Bingqing Gao; Liu Zhang; Yanmin Wang; Junnan Ma; Xingchen Wu; Chenyu Zhou; Min Liu; Lin Zhang (Journal of Ovarian Research)
Abstract Background Cisplatin (DDP) is one of the most effective anticancer drugs, commonly used to treat advanced ovarian cancer (OC). However, DDP has significant limitations of platinum-based drugs, including chemical resistance and high-dose toxic side effects. Traditional Chinese medicines (TCMs) often presented in the form of formula, in which the herb pair was the basic unit. Scutellaria barbata D.Don and Hedyotis diffusa Willd (SB-HD) are famous TCMs herb pair that have been shown to help treat multiple types of cancers. However, the synergistic effects and mechanism of combination of SB-HD and DDP to enhance DDP chemosensitivity in OC are still unknown. Results In vitro, we found that the optimal proportion of SB-HD to inhibit the proliferation of OC cells was 2:1, SB-HD and DDP were shown to synergistically reduce the viability of OC cells, inhibit the colony formation, promote cell cycle arrest and apoptosis, as well as inhibit cell migration and invasion. In vivo, combination treatment significantly inhibited the growth of subcutaneous tumors in BALB/c nude mice and reduced the toxic side effects of DDP. Mechanistically, SB-HD and DDP combination treatment significantly promoted oxidative stress response, decreased MMP, inhibited ATP production, decreased ROS levels and increased SOD activity, increased the expression of NRF2, HO-1, ATG5 and LC3, decreased the expression of p62 and FTH1 both in OC cells and tumor tissue of mice. Inhibitor 3-MA (Methyladenine, autophagy inhibitor) and Fer-1 (Ferrostatin-1, iron ion inhibitor) can effectively reverse the expression changes of the key target proteins, but not ZnPP (Zinc protoporphyrin, HO-1 inhibitor). Through bioinformatics analysis, it was found that the abnormal expression level of NRF2 and FTH1 mRNA has a high prognostic value, at the same time, the other four key proteins respectively or interacting with NRF2 and FTH1, also play important roles in the occurrence and development of OC. Conclusion Our findings uncover a synergistic effect of SB-HD and DDP against OC through modulating oxidative stress via NRF2-FTH1 autophagic degradation pathway, which may provide an important theoretical foundation for the use of SB-HD and a new strategy for enhancing DDP chemosensitivity as well as reducing toxic side effects.